A cross country comparison for the burden of cardiovascular disease attributable to tobacco exposure in China, Japan, USA and world - Xiaomei Wu; Bo Zhu; Shuang Xu; Yifei Bi; Yong Liu; Jingpu Shi (BMC, 2020)
Abstract Background Tobacco exposure (TE) is the major contributor for CVD mortality, but few published studies on CVD mortality attributable to TE have analyzed the potential reasons underlying long-term trends in China. Our studysought to find the potential reasons and compared CVD mortality attributable to TE in China, Japan, the United States of America (USA), and the world between 1990 and 2017. Methods The mortality data in China, Japan, the USA, and the world were obtained from Global Burden of Disease Study 2017(GBD 2017). Joinpoint regression was used to assess the trend magnitude and directions over time for CVD mortality, while the age-period-cohort method was used to analyzethe temporal trends of CVD mortality according to age, period, and cohort. Results A significant downward trend was found in the age-standardised mortality rate (ASMR) of CVD attributable to smoking in four regions. China had the smallest decline and the Chinese ASMR became the highest in 2017. All the annual net drifts in the four regions were negative and the local drifts were below zero. The longitudinal age curves of CVD mortality attributable to smoking increased in four regions,with China having the largest increase. The period or cohort RRs indicated a decline, and China had the smallest decline. The researchers further analyzed the IHD and stroke trends, finding that the morality and period or cohort RR of IHD in China was always at a high level. Conclusions CVD mortality attributable to TE declined in four regions, and was highest in China. The proportion of IHD mortality attributable to TE was similar to stroke, which significantly changed the traditional cognition of CVD composition, but the control measure was not sufficient for IHD in China.